Quantitative and qualitative feed restriction for broilers (Research, Society and Development, 2021)
The objective of this study is to evaluate the influence of five feed restriction programs (FRP) on broiler performance and carcass yield. 425 Cobb 500® broilers were distributed in a completely randomized design with five FRPs and five replicates with 17 broilers. The FRPs were: Program 1 (P1): consumption ad libitum (AL) of control diet from 14 to 42 days; P2: quantitative restriction (QTR) of 10% of AL consumption from 14 to 28 days and AL consumption from 29 to 42 days; P3: AL consumption from 14 to 28 days and QTR from 29 to 42 days; P4: qualitative restriction (QLR) of 10% of the level of crude protein and essential amino acids from 14 to 28 days and AL consumption from 29 to 42 days; and P5: AL consumption from 14 to 28 days and QLR from 29 to 42 days. The broilers of the AL treatment gained more weight (p≤0.01), but had a similar FCR (P>0.05) compared to broilers submitted to QTR from 29 to 42 days. In addition, broilers fed QTR from 14 to 28 days presented a lower FI and a better FCR (p≤0.01) in relation to broilers fed QLR of 14 to 28 (P4) and 29 to 42 days (P5). The broilers fed QTR of 14 to 28 days diet presented a similar FCR as broilers fed AL. The 10% reduction in AL consumption of 14 to 28 d is a viable economical alternative to feed broilers up to 42 days of age.